High rate capability studies of triple-GEM detectors for the ME0 upgrade of the CMS muon spectrometer. (1st February 2022) - Bianco, M.; Fallavollita, F.; Fiorina, F.; Maggi, M.; Pellecchia, A.; Ramirez Garcia, L.F.; Rosi, N.; Verwilligen, P.; ,
Abstract: The high-luminosity LHC (HL-LHC) upgrade is presenting new challenges for particle detector technologies. In the CMS muon system gaseous detectors, the increase in luminosity will produce a particle background ten times higher than at the LHC. To cope with the high rate environment and maintain current performance, the triple-gas electron multiplier technology is a promising candidate for high-rate capable detectors for the CMS-ME0 upgrade project in the innermost region of the forward muon spectrometer of the CMS experiment. An intense R&D and prototyping phase is currently ongoing to prove that such technology meets the stringent performance requirements of highly efficient particle detection in the harsh background environment expected in the innermost ME0 region. Here, we describe the recent rate capability studies of triple-GEM detectors operated with an Ar/CO2  (70/30) gas mixture at an effective gas gain of 2 × 10 4 by using a high intensity 22 keV X-ray generator. Moreover, we present a novel foil design based on double-sided segmented GEM-foils, high voltage power distribution and filtering, which the CMS muon collaboration adopted for realization of the CMS-ME0 project, and their impact on the performance of the detector in the light of new rate capability studies, with a summary of the ongoing R&D activities.